2020
DOI: 10.1186/s12245-020-00323-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a financial incentive on the completion of educational metrics

Abstract: Background The Accreditation Council for Graduate Medical Education (ACGME) requires all emergency medicine (EM) training programs to evaluate resident performance and also requires core faculty to attend didactic conference. Assuring faculty participation in these activities can be challenging. Previously, our institution did not have a formal tracking program nor financial incentive for participation in these activities. In 2017, we initiated an educational dashboard which tracked and published all full-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In the second of the five papers, Pugh et al reported that providers who achieved both of the pre-set benchmarks for evaluation completion and attendance were to be monetarily incentivized each quarter [ 22 ]. Faculty significantly achieved/exceeded expectations for percent completion of resident evaluations and did so in a shorter time frame.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In the second of the five papers, Pugh et al reported that providers who achieved both of the pre-set benchmarks for evaluation completion and attendance were to be monetarily incentivized each quarter [ 22 ]. Faculty significantly achieved/exceeded expectations for percent completion of resident evaluations and did so in a shorter time frame.…”
Section: Reviewmentioning
confidence: 99%
“…Many, it seemed, were published as proof of concept papers, demonstrating that an MBM approach to the education mission was possible, albeit complex. Others demonstrated some improvements in specific aspects of an educational program (e.g., completion of learner evaluations [ 22 ]) associated with some effort to incentivize the desired behaviors. The nature of the papers was such that often there was not a clear methods section, so we had to infer that certain measures were made, even if they were not described.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The article also underscores the importance of addressing faculty concerns, introducing incentives, and incorporating machine learning to enhance the tool's efficiency and overcome current limitations. [4][5][6] The study's strengths lie in the innovative approach, comprehensive methodology, and the potential to improve surgical education through improved feedback with this technology. However, for a larger implementation, this proposal needs to overcome significant challenges including faculty resistance, the need for standardization, and ensuring diversity in faculty participation.…”
mentioning
confidence: 99%